E04 Cortical Thinning Of The Occipital Lobe In Huntington's Disease And Associations With Cognitive Performance. (17th September 2014) - Johnson, EB; Rees, EM; Labuschagne, I; Durr, A; Leavitt, BR; Roos, RAC; Johnson, H; Hobbs, NZ; Crawford, HE; Langbehn, DR; Stout, JC; Tabrizi, SJ; et al.
Abstract : Background: Previous Huntington's disease studies have revealed occipital lobe atrophy and cortical thinning, although it is unclear when this develops and whether it is uniform across the lobe. Visual deficits are not typical of HD symptomatology, however it is possible that more subtle visual functions are impaired and, in turn, influence performance on cognitive tasks with a visual component. Aims: To identify the regional distribution of disease-related occipital cortical thinning and investigate associations with cognitive and motor impairment. Methods: T1-weighted 3T MR scans from controls (n = 107), pre-HD (n = 116) and early HD subjects (n = 90) from the TRACK-HD study were processed using the FreeSurfer software; cuneus, pericalcarine, lingual and lateral occipital regions were outputted. Generalised least squares regression models were fitted to assess between-group differences. Relationships between visual cognitive and motor task performance and cortical occipital thinning in gene-positive participants were assessed using general linear regression models. Results: The occipital cortex was significantly thinner in pre-HD and early HD participants. These between-group differences were heterogeneous across regions, with the lateral occipital region showing the most pronounced effects. Significant associations were found between reduced occipital cortical thickness and poorer performance on a number of cognitive tasks involving a visual component. No association was found with finger tapping. Conclusions: Regionally-specific thinning of the occipital cortex was evident more than a decade before estimated HD symptom onset. Associations were found with cognitive tasks, but not finger tapping, suggesting that occipital thickness plays an important role in cognitive tasks with a visual component. This has implications for the interpretation of impaired cognitive performances in HD, which is typically attributed to frontal and executive circuits, rather than to visual regions.